Documental “Skate Turístico - Gindeya Muñoz, Amir Mustafa (2012)
In Ecuador, skating or "skateboarding" as most people know it is a sport that in the passage of years has been growing in all areas of the country, but particularly in two cities in the country that are of Quito and Guayaquil and two other small towns that are Portoviejo and Riobamba. The documentary "Skate Tour" is a documentary focusing on the cities of Ecuador show from the perspective of a skater in this way breaking the paradigm of the classic structure of skating video and the video tour and showing the modus vivendi of a local skater also know more sobrea each city with interviews with two skaters Ecuadorians are great exponents in skating. Thus the documentary "Skate Tour" show what the Ecuadorian skater wants to see or know all this with new techniques and trends in image color and video, also the use of visual effects.